The Significance of the definition of annexation in the Holy Quran in the Almighty’s saying ) فاسألوا أهلَ الذكرِ إنْ كنتم لا تعلمون(between the purpose of the Holy Quran and the comprehension of the interpreters - assistant lecturer : Hussain Salih Dahir (Journal of College of Education, 2024)
The Holy Quran used and appointed the characteristics of the Arabic language, the methods of speech and the communicative speech to show the meaning and the purpose of the versus, furthermore the grammatical structure are used to explain and show the accuracy of the meaning, one of these structures which is mention in the Holy Quran is defining and non -defining. This research shows the function and the purpose of the genitive which is shown by the expression “ask of those who posses the message” “ahla althikr “ , it also shows its linguistic function and how it became a special semantic linguistic signal that leads to its linguistic and rhetorical purpose that indicates the position of the prophet “ peace upon him ” that God signaled out for him and how the interpreters explain that the expression “ask of those who posses the message” is not specific to the Messenger